2019
DOI: 10.1002/smj.3061
|View full text |Cite
|
Sign up to set email alerts
|

Is your playing field unleveled? U.S. defense contracts and foreign firm lobbying

Abstract: Research Summary Prior research in political strategy shows that political capital is critical in achieving desirable nonmarket strategy outcomes. Less attention has been paid to the fact that firms vary in their ability to acquire political capital. Foreign firms, which typically suffer from the liability of foreignness, have difficulty acquiring and strengthening political capital in a host country. Drawing on the literatures on political capital, the liability of foreignness, and certification, I argue that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 103 publications
0
49
0
Order By: Relevance
“… For instance, lobbying has been one of the most widely studied corporate political action initiatives in the US context. However, the keyword search in our database results in only 11 papers on cross-border corporate lobbying (e.g., Barron, et al, 2017 ; Kim, 2019 ; Weil, 2018 ). On the other hand, we suspect that a significant number of multinational CPA articles (especially those that explore political ties and MNE–host government relationships) do cover MNE “lobbying” activities, but they simply do not use this terminology.…”
Section: Notesmentioning
confidence: 99%
“… For instance, lobbying has been one of the most widely studied corporate political action initiatives in the US context. However, the keyword search in our database results in only 11 papers on cross-border corporate lobbying (e.g., Barron, et al, 2017 ; Kim, 2019 ; Weil, 2018 ). On the other hand, we suspect that a significant number of multinational CPA articles (especially those that explore political ties and MNE–host government relationships) do cover MNE “lobbying” activities, but they simply do not use this terminology.…”
Section: Notesmentioning
confidence: 99%
“…Our supplemental analyses also speak to the effectiveness of firms’ political activities (Mizruchi, 1992; Ridge, Ingram, and Hill, 2017; Kim, 2019). Recent research has questioned whether simple measures of numbers of lobbyists or campaign contributions are sufficient to explain outcomes for firms (Hill et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Eden and Miller (2004) break LOF down into three categories: unfamiliarity, discrimination, and relational hazards, which clearly align with the social, political, and institutional aspects of LOF. A lack of legitimacy, coupled with information asymmetry and economic nationalism in host countries, gives rise to a lack of trust in foreign firms and sometimes discrimination against them (Baik et al, 2013;Elango, 2009;Kim, 2019;Kim & Jensen, 2014;Krug & Hegarty, 2001;Li, 2008;Li, Poppo, & Zhou, 2008;Obadia, 2013;Wu & Salomon, 2017).…”
Section: From Costs Of Doing Business Abroad To Lofmentioning
confidence: 99%
“…Beyond economic calculations, sociological perspectives stress social and relational context as a driver of LOF. The social capital/network perspective emphasizes the lack of embeddedness of foreign subsidiaries in local networks (Mezias, 2002a(Mezias, , 2002bJohanson & Vahlne, 2009;Kim, 2019) and the need to develop ties with host-country stakeholders to alleviate the relational hazards of LOF (Rangan & Drummond, 2004;Li et al, 2008;Guo et al, 2018;Valentino et al, 2018). Since Zaheer's (1995) original empirical study, other ones have found that LOF is likely to have a negative impact on MNE performance.…”
Section: Foreignness Assetsmentioning
confidence: 99%